Investigation of the Electromagnetic Wave-Tissue Interaction of a 75–110 GHz Reflective Resonator Probe for Tissue Classification - Hecht, Damaris; Pfahler, Tim; Vossiek, Martin (2024 54th European Microwave Conference (EuMC), 2024)
In this work, the interaction of a 75–110 GHz reflective resonator probe with biological tissue is investigated for both tactile and non-contact measurements. A proof of concept of the principle and an approach for highly accurate tissue classification were provided in previous work – for tactile in vivo measurements. However, for some classification tasks, such as the assessment of burn wounds, non-contact measurements are preferable. The next step towards a non-contact application is therefore to investigate how distances between the probe tip and the tissue surface affect the field distribution in the tissue and the reflectance spectra measured by the probe, as the spectra form the basis for subsequent tissue classification. In this work, the setup of the probe was modeled for different distances to the skin surface, from 0–1 mm. The resulting electric field distribution in the tissue and the reflection coefficient spectra are presented and discussed. Based on the simulation results, the existing classification concept is suitable for non-contact measurements with small distances of 0.1 mm or less.
Created from Fastlane, Scopus look-up
Keywords: biomedical sensing; burn wound assessment; millimeter-wave near-field spectroscopy; resonant sensor; tissue classification; tissue modeling; wave-tissue interaction